An Analysis of Monetary Policy in Controlling the Monetary Assets in Pakistan: A Money Multiplier Approach (1971-72 to 1989-90) (The Pakistan Development Review, 1993)
Besides fiscal policy, monetary policy is designed to attain sustained economic growth and to contain inflation within manageable limits. Usually monetary policy is pursued through variations in money supply in accordance with the requirement of output level and employment on one hand and price stability on the other. In Pakistan monetary policy is formulated to control total monetary assets keeping in view the projected growth rate of GDP, monetisation of the economy and the likely surplus or deficit in the country's international account. Once the safe limit of total monetary assets is determined it is then realised through different indirect measures, namely, the liquidity ratio, reserve requirements and the bank rate. l?rior to 1972 credit was controlled by these indirect measures. However, the separation of the Eastern wing and the two oil shocks of the early 1970's indicated the shortcomings of indirect methods when they failed to cope with the new situation. The open market operation could not be materialised due to marginal or nominal demand of government securities. The credit budgeting measure was introduced in 1972, replacing the old one, wherein the principal instrument is the credit ceiling for the commercial banks and they are bound to allocate credit to the priority sectors as determined by the government. Credit budgeting has proved to be an effective instrument of monetary policy both as a means of providing necessary funds for the development process and for curbing the increasing trends in prices. The credit ceiling with· its beneficial effects also has some adverse effects for example, commercial banks have little incentive in mobilising deposits, and their ability to respond to demand becomes extremely limited. The response of the public and commercial banks, to a certain extent, depend upon the credit ceilings determined by the monetary authority.